Friend or foe? Mitochondria as a pharmacological target in cancer treatment. (December 2017) - Dickerson, Tyler; Jauregui, Catherine E; Teng, Yong
Mitochondria have acquired numerous functions over the course of evolution, such as those involved in controlling energy production, cellular metabolism, cell survival, apoptosis and autophagy within host cells. Tumor cells can develop defects in mitochondrial function, presenting a potential strategy for designing selective anticancer therapies. Therefore, cancer has been the main focus of recent research to uncover possible mitochondrial targets for therapeutic benefit. This comprehensive review covers not only the recent discoveries of the roles of mitochondria in cancer development, progression and therapeutic implications but also the findings regarding emerging mitochondrial therapeutic targets and mitochondria-targeted agents. Current challenges and future directions for developments and applications of mitochondrial-targeted therapeutics are also discussed.